Causes of Death and Conditional Survival of Renal Cell Carcinoma - Shao, Ning; Wan, Fangning; Abudurexiti, Mierxiati; Wang, Jun; Zhu, Yao; Ye, Dingwei (Frontiers in Oncology, 2019)
Background: As conditional survival could provide more relevant prognostic information at each follow-up time, the present study was to assess conditional overall survival (COS) based on two cohorts and assess the risks of death due to RCC vs. other causes. Methods: Fudan University Shanghai Cancer Center (FUSCC) and SEER database were used as the source of data for our analysis. COS and cancer-specific survival were evaluated using the Kaplan-Meier method. Results: A total of 90927 patients (SEER cohort = 88807, FUSCC cohort = 2120) were enrolled. Our results suggested that hazards of other causes-related death were always higher than that of cancer-specific death in low-risk RCC patients, but lower in metastatic RCC patients. It exceeded that of cancer-specific death by 8 years in high-risk RCC patients. Only in metastatic RCC patients, the COS improved markedly with survivorship increasing. After surviving 1, 2, 3, 4 and 5 years, the 5-years COS increased by +10, +18, +23, +29 and 35% (the observed 5-years OS: 12%), respectively. Conclusions: COS can better to help patients with metastatic RCC rather than other RCC patients. Additionally, COS brings optimism for metastatic RCC patients with expected poorer prognosis psychologically.